MicroRNA-27b alleviates septic cardiomyopathy by targeting the Mff/MAVS axis - Wang, Xincai; Huang, Long; Xu, Jingqing; Li, Min; Zhang, Hongxuan; Yao, Yuqing; Liu, Yaqing; Lin, Xingsheng; Shang, Xiuling (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo investigate the protective role of microRNA-27b (miR-27b) in septic cardiomyopathy (SCM) and its regulatory mechanism on the mitochondrial fission factor (Mff)/mitochondrial antiviral signaling protein (MAVS) axis.MethodsTranscriptome data from septic patients’ cardiac tissues (GSE79962) were analyzed. Serum miR-27b expression was measured in SCM patients (n=11), sepsis-only patients (n=22), and healthy controls (n=30). Mouse SCM model and HL-1 cardiomyocyte model were established by lipopolysaccharide (LPS) induction. The molecular mechanism was investigated using miR-27b agonist/antagonist and Mff intervention, combined with RT-qPCR, Western blot, immunofluorescence, and transmission electron microscopy.ResultsBioinformatics analysis revealed significant downregulation of miR-27b in SCM cardiac tissues (log2FC=-3.9, P<0.001). Clinical validation showed lower miR-27b expression in SCM patients’ serum compared to sepsis-only patients and healthy controls (P<0.05). LPS-induced SCM model exhibited cardiac dysfunction, myocardial injury, mitochondrial abnormalities, decreased miR-27b expression, and increased Mff and MAVS levels. miR-27b targeted Mff to maintain mitochondrial homeostasis, thus attenuating LPS-induced cardiomyocyte inflammation and apoptosis, while Mff overexpression reversed this protective effect.ConclusionmiR-27b alleviates myocardial injury and inflammation in SCM by targeting the Mff/MAVS axis to maintain mitochondrial homeostasis, representing a potential novel therapeutic target for SCM.